Ne- and O2-filled ice XVII: a neutron diffraction study. Issue 27 (19th June 2019) - Catti, Michele; del Rosso, Leonardo; Ulivi, Lorenzo; Celli, Milva; Grazzi, Francesco; Hansen, Thomas C.
Abstract : Ne and O2 molecules are hosted by ice XVII in disordered spiral-like arrangements within the hexagonal channels. Abstract : Deuterated ice XVII, a metastable solid water polymorph, was filled with Ne and O2 at p ≈ 100 kPa and studied by in situ neutron diffraction (ILL, France). Powder patterns were collected in the ranges of 20–50 K (Ne) and 4.6–90 K (O2 ). Rietveld refinement and difference Fourier techniques showed that the gas molecules were located inside the hexagonal channels of the host ice. Both Ne atoms and O2 molecules are arranged in a spiral-like configuration off the channel axis, preserving the P 61 22 symmetry of the host in the case of Ne, but reducing it to P 61 in O2 . A larger Ne absorption compared to Ne-filled ice II is observed, which is consistent with longer host–guest contacts producing smaller hydrophobic repulsion. In O2 -filled ice XVII, instead, short O–D distances (2.37 Å) have attractive character and stabilize the structure.